Knowledge, attitudes and practices of teachers, administrators and supervisors on the scheme of continuous progression in the Division of Cebu City - Reynes, Josefina F. 1946- (1975)
Data obtained from 520 teachers, 37 principals/head teachers and 12 supervisors were analyzed using percentages, critical ratio, t-test and chi-square test. The respondents know that the scheme is a system where children are taught according to their achievement levels and that it was adopted mainly because it provides for individual differences. They realize that the administrator's job under the scheme is to plan, administer the organizational scheme in the school and to continuously observe as well as update the diagnosis of pupils skills and abilities. They also recognize that the supervisors' responsibility under the scheme is to conduct inservice education for the principals and teachers, as well as to identify and recommend instructional materials needed to meet different skills of learners.
Thesis (M.Ed.)--University of the Philippines
Keywords: Education -- Experimental methods; Educators -- Philippines